IL-33 accelerates cutaneous wound healing involved in upregulation of alternatively activated macrophages - Yin, Hui; Li, Xiangyong; Hu, Shilian; Liu, Tao; Yuan, Baohong; Gu, Hongbiao; Ni, Qian; Zhang, Xiaofan; Zheng, Fang (Molecular immunology, 2013)
•We examined the role of IL-33 in mucosal healing and epithelial restoration and repair.•The expression of IL-33 is enhanced in incisional wound skin.•Administration of exogenous IL-33 accelerates wound healing.•IL-33 promotes collagen deposition and ECM synthesis.•The effect of IL-33 is associated with upregulation of alternatively activated macrophages (AAM). IL-33 is a recently recognized member of the IL-1 family and has been best identified as a potent inducer of Th2-type immune responses. Increasing evidence, however, indicates that IL-33 also represents an important mediator of mucosal healing and epithelial restoration and repair. In this study, we further explore the potential effect of IL-33 in cutaneous wound healing. A full-thickness skin wound was generated on the back of mice and treated with IL-33 or vehicle intraperitoneally. Our results revealed that the levels of IL-33 mRNA and protein were significantly enhanced in incisional wound skin. Meantime, administration of IL-33 obviously accelerated wound healing with wounds gaping narrower and exhibiting enhanced reepithelialization. IL-33 upregulation also promoted the collagen deposition and the expression of extracellular matrix (ECM)-associated genes such as fibronectin and collagen IIIa, which implies a direct effect of IL-33 on matrix synthesis. Furthermore, IL-33 facilitated the development of alternatively activated macrophages (AAM) in incisional wound tissue, which closely related to resolution of inflammation and promotion of wound repair. Taken together, these findings suggest that IL-33 may play a pivotal role in maintenance of cutaneous homeostasis and acceleration of normal wound healing.